Broker bureaucracies: The subsidiary offices of the digitalizing state - Fenna Imara Hoefsloot; Neha Gupta; Dennis Mbugua Muthama; José de Jesús Flores Durán (Digital Geography and Society)
Intermediaries play crucial roles in the implementation and functioning of the state in the transition towards digital governance. As a restructuring of networks, information flows, and territories – the digitalizing state implies the transition towards the digitalized interaction between the state and its residents, signaling a potential shift in the position of intermediaries in this process. Drawing on interviews with brokers and key informants in land administration and ethnographic observations in Nairobi, Guadalajara, and Mumbai, we explore the interplay between digital technologies, paper-based systems, typists, consultants, and citizens in the digitalizing state. This urges us to consider how digitalization, in many ways, goes against the novelty and excitement ascribed to the dynamics of modernizing and digitizing state governance. Paying attention to the geographies of information flows shows how digitalization unfolds in both the offices of the state as well as in subsidiary, hybrid spaces and through acts of brokerage. We argue that the paper-filled offices of the print shops and cybercafés are the sites where a potentially different range of alternative digital futures are exposed. Outside of the tropes of control, seamless connection, or the globalizing effect of digital technologies, these spaces give insight into the deeply institutionalized cultures and ways of organizing civil and political life in which digital technologies are introduced.